Base glass and preparation method thereof, glass powder, granulation powder, glass insulator, radio frequency glass insulator and radio frequency connector
By optimizing the ingredients and proportion of the glass insulator in the radio frequency connector, the problems of glass melting and clarification of difficulty, high dielectric constant and high dielectric loss have been solved. High -frequency signal transmission.
Patent Information
- Application Number
- CN202411495228.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
AI Technical Summary
The glass insulators in existing RF connectors have difficulties in melting and clarifying, and have high dielectric constant and dielectric loss, which limits their application in high-frequency signal transmission.
A basic glass, its composition includes SIO2, B2O3, Al2O3, K2O, LI2O, and SNO2. By controlling the content and proportion of these ingredients, the network structure and chemical stability of the glass are optimized, thereby reducing the dielectric constant and dielectric loss.
The low -agent constant and low -agency electric loss of the glass are realized, the chemical stability and clarification effect of the glass are improved, and it is suitable for high -frequency RF connectors, which improves the quality of signal transmission quality and the service life of the device.
Smart Images

Figure CN119371099A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of radio frequency connectors, and in particular to a basic glass and a preparation method thereof, glass powder, granulation powder, a glass insulator, a radio frequency glass insulator and a radio frequency connector. Background Art
[0002] With the advent of the 5G / 6G communication era and the era of rapid development of modern science and technology, RF connectors, as key components in the communication field, are mainly used to transmit high-frequency signals and are widely used in 5G base stations, radar navigation systems, satellites, radio and television, medical, measurement, automobiles, smart devices, consumer electronics and many other fields. The anti-interference ability and high-frequency transmission ability of RF connectors are determined by RF glass insulators. RF glass insulators are composed of shells, pins, and glass insulators. The shells and pins are both Kovar alloys. Glass insulators usually choose glass with low dielectric constant and low dielectric loss. Low dielectric properties can avoid interference with signals during transmission and ensure the quality of signal transmission. Low dielectric loss can avoid excessive heat consumption due to heating of devices at high frequencies. At present, DM305 / 308 type glass is generally used in China. Although the expansion coefficient is very compatible with Kovar alloy, the dielectric constant is high. In addition, the quality of glass is unstable, which leads to large fluctuations in product performance, which in turn leads to severe restrictions on its use. With the increasing demand for high-frequency signals, glass with lower dielectric constant and dielectric loss is needed to replace existing products. In addition, with the demand for increasingly smaller and lighter devices, the glass in RF glass insulators accounts for 50% of the overall weight, so the density of the glass itself also directly affects the weight of the final device.
[0003] There are also related patents in China that mention glass insulators for RF connectors. Among them, the Chinese patent application with patent application number 201811611320.5 mentions a low dielectric constant glass. Although the dielectric constant can be as low as 3.6, the glass component contains Na and CaF2. Na + Ions and Ca 2+ The presence of ions makes the signal unstable and the device easily heats up due to the rapid movement of cations during use. The Chinese patent application with patent number 202110446122.3 mentions a miniature RF glass insulator with a low dielectric constant sealing glass powder. The dielectric constant can be as low as 3.8 and the dielectric loss can be as low as 0.0004. Although the dielectric constant and dielectric loss are also very low, the glass component also contains Na + ions, which move rapidly during use, causing fluctuations in dielectric properties, and Ga 3+ , P 5+ ,La 3+Ions of equal and large radius will increase the density of the glass itself, so it is not conducive to the lightweighting of the end product.
[0004] Low dielectric constant and low loss glass generally adopts high borosilicate glass system. Although it has excellent performance, it also has some technical difficulties. High borosilicate glass is mainly composed of silicon oxide and boron oxide. In order to achieve low dielectric and low loss performance, the content of both must be increased, which makes it difficult to melt and clarify the glass, and the bubbles generated during the melting process are difficult to discharge, and ultimately high-quality glass products cannot be obtained; in addition, higher silicon oxide and boron oxide are very likely to cause glass phase separation, which seriously affects the chemical stability of the glass, especially acid resistance; in addition, in order to reduce the melting temperature of the glass, manufacturers add Na elements or elements with a larger specific gravity. This glass can indeed reduce the melting temperature of the glass, but it also has an adverse effect on the performance of the product, such as increased specific gravity and poor dielectric properties. Summary of the invention
[0005] The main purpose of the present invention is to provide a basic glass and a preparation method thereof, glass powder, granulation powder, glass insulator, radio frequency glass insulator and radio frequency connector to solve the problems of difficult melting and clarification of glass and high dielectric constant and dielectric loss in the prior art.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a base glass is provided, which comprises the following components, in molar percentage: SiO2 with a content of 72-74%, B2O3 with a content of 20-25%, Al2O3 with a content of 0.1-0.5%, K2O with a content of 0.5-1%, Li2O with a content of 1.8-2.2%, and SnO2 with a content of 0.01-0.1%.
[0007] Furthermore, the molar ratio of the above-mentioned K2O to SnO2 is 10-20:1; and / or the molar ratio of SiO2 to B2O3 is 1:0.32-0.33.
[0008] Furthermore, the dielectric constant of the base glass at 25°C and 1MHz is 3.5-3.6, and the dielectric loss is 0.0001-0.0003; and / or the density of the base glass is 2.0400-2.0700 g / cm 3 .
[0009] According to another aspect of the present invention, a method for preparing the aforementioned basic glass is provided, the method comprising: mixing raw materials including Si source, B source, Al source, K source, Li source and Sn source, and then sequentially performing melting treatment and molding to obtain basic glass.
[0010] Furthermore, the temperature of the above-mentioned melting treatment is 1530-1580° C.; and / or the time of the melting treatment is 5-10 hours.
[0011] Furthermore, the Si source is quartz sand; and / or the B source is boron gangue and / or boric acid; and / or the Al source is aluminum oxide and / or aluminum hydroxide; and / or the K source is selected from any one or more of KNO3, KF and KCl; preferably the K source is KF and / or KCl; and / or the Li source is Li2CO3; and / or the Sn source is tin dioxide.
[0012] According to another aspect of the present invention, a glass powder is provided, which includes a basic glass powder, and the basic glass powder is prepared by subjecting the aforementioned basic glass to a pulverizing treatment, wherein the pulverizing treatment is preferably a ball milling treatment, and the rotation speed of the ball milling treatment is 250 to 400 rpm; and / or the ball milling treatment time is 2 to 10 hours.
[0013] Furthermore, the above-mentioned glass powder also includes an additive, and the mass ratio of the additive to the basic glass powder is 0.5 to 1:100; preferably, the D50 of the additive is 50 to 500 nm; and / or the D50 of the basic glass powder is 2 to 15 μm; preferably, the additive is nano-alumina and / or nano-zirconium oxide; preferably, the additive is a combination of nano-alumina and nano-zirconium oxide, and the mass ratio of nano-alumina to nano-zirconium oxide is 1:1 to 5.
[0014] According to another aspect of the present invention, there is provided a granulated powder, which is obtained by preparing a slurry of the aforementioned glass powder with a binder and water, and then granulating the slurry.
[0015] According to another aspect of the present invention, a glass insulator is provided, which is prepared by sequentially subjecting granulated powder to pressing, debinding and sintering treatments, and the granulated powder is the aforementioned granulated powder.
[0016] According to another aspect of the present invention, a radio frequency glass insulator is provided, comprising a shell, a pin and a glass insulator, wherein the glass insulator is the aforementioned glass insulator.
[0017] According to another aspect of the present invention, a radio frequency connector is provided, wherein the radio frequency connector contains the radio frequency glass insulator described above.
[0018] Using the technical solution of the present invention, SiO2 and B2O3 are used as network formers of the base glass, wherein SiO2 is the main component of the base glass and exists in the form of [SiO4], while B2O3 exists in the form of [BO3] and [BO4], wherein [BO4] is connected with [SiO4] to make the glass network structure more stable, which is beneficial to improving the chemical stability of the base glass; on the other hand, since the network structure of SiO2 and B2O3 is relatively stable and the covalent bonds are relatively strong, it is difficult for electrons and ions to move or undergo significant polarization reactions, thus significantly reducing the dielectric constant of the glass. Al2O3, as a filler of the network structure, helps to adjust the chemical stability of the base glass and helps to reduce the phase separation of the glass. K2O and Li2O, as network exosomes of the glass, will destroy the network structure of the glass, which helps to reduce the melting point of the glass and improve the clarification effect of the glass. In addition, K + Ions have a larger ionic radius than Na + The ions are large, so their movement in the limited glass network structure is restricted, so their impact on the dielectric constant is greater than that of Na + Ions should be low; Li + The ionic radius is the smallest among alkali metals, and the polarization ability is weak. It can be tightly combined with the silicon-oxygen bond in the glass network structure, thereby reducing the polarization ability of the glass. Therefore, a small amount of addition will not have a significant impact on the dielectric constant of the glass. At the same time, it can also effectively reduce the melting temperature of the glass and improve the chemical stability. SnO2 is added to the glass as a glass clarifier, and the bubbles in the glass are eliminated by high-temperature decomposition and release of oxygen. It is preferred to control the content of the above components within the above range, which helps to give full play to the synergistic effect between the components, thereby helping to improve the chemical stability of the base glass and reduce the dielectric constant and dielectric loss of the base glass. In particular, controlling the content of K2O to 0.5-1% and the content of SnO2 to 0.01-0.1% helps to give full play to the synergistic effect between the two, thereby helping to reduce the melting temperature of the base glass and improve the clarification effect of the base glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0020] Figure 1 An optical photograph of the granulated powder of the present application is shown;
[0021] Figure 2 An optical photograph of the glass insulator of the present application is shown. DETAILED DESCRIPTION
[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0023] As analyzed in the background technology of this application, the glass in the prior art has the problems of difficulty in melting and clarifying, as well as high dielectric constant and dielectric loss. In order to solve the above problems, this application provides a basic glass and a preparation method thereof, glass powder, granulation powder, glass insulator, RF glass insulator and RF connector.
[0024] In a typical embodiment of the present application, a base glass is provided, which includes the following components, in molar percentage: 72-74% SiO2, 20-25% B2O3, 0.1-0.5% Al2O3, 0.5-1% K2O, 1.8-2.2% Li2O, and 0.01-0.1% SnO2.
[0025] SiO2 and B2O3 are network formers of the basic glass. SiO2 is the main component of the basic glass and exists in the form of [SiO4], while B2O3 exists in the form of [BO3] and [BO4], where [BO4] and [SiO4] are connected to make the glass network structure more stable, which is beneficial to improve the chemical stability of the basic glass. On the other hand, since the network structure of SiO2 and B2O3 is relatively stable and the covalent bonds are relatively strong, it is difficult for electrons and ions to move or undergo significant polarization reactions, which can significantly reduce the dielectric constant of the glass. Al2O3, as a filler in the network structure, helps to adjust the chemical stability of the basic glass and helps to reduce the phase separation of the glass. K2O and Li2O, as network exogenous bodies of the glass, will destroy the network structure of the glass, help to reduce the melting temperature of the glass and improve the clarification effect of the glass. In addition, K + Ions have a larger ionic radius than Na + The ions are large, so their movement in the limited glass network structure is restricted, so their impact on the dielectric constant is greater than that of Na + Ions should be low; Li +The ionic radius is the smallest among alkali metals, and the polarization ability is weak. It can be tightly combined with the silicon-oxygen bond in the glass network structure, thereby reducing the polarization ability of the glass. Therefore, a small amount of addition will not have a significant impact on the dielectric constant of the glass. At the same time, it can also effectively reduce the melting temperature of the glass and improve the chemical stability. SnO2 is added to the glass as a glass clarifier, and the bubbles in the glass are eliminated by high-temperature decomposition and release of oxygen. It is preferred to control the content of the above components within the above range, which helps to give full play to the synergistic effect between the components, thereby helping to improve the chemical stability of the base glass and reduce the dielectric constant and dielectric loss of the base glass. In particular, controlling the content of K2O to 0.5-1% and the content of SnO2 to 0.01-0.1% helps to give full play to the synergistic effect between the two, thereby helping to reduce the melting temperature of the base glass and improve the clarification effect of the base glass.
[0026] In one embodiment of the present application, the molar ratio of K2O to SnO2 is 10-20:1; and / or the molar ratio of SiO2 to B2O3 is 1:0.32-0.33.
[0027] A molar ratio of K2O to SnO2 that is too large or too small is not conducive to improving the clarification effect of the base glass. It is preferred to control the molar ratio of K2O to SnO2 within the above range, which is helpful to make the base glass have a better clarification effect and a lower melting temperature, thereby helping to reduce the production cost of the base glass and improve the melting quality of the base glass, and is also helpful to reduce the density of the base glass. A molar ratio of SiO2 to B2O3 that is too large is not conducive to the melting and clarification of the base glass, and a molar ratio of SiO2 to B2O3 that is too small is not conducive to the chemical stability of the base glass. It is preferred to control the molar ratio of SiO2 to B2O3 within the above range, which is helpful to ensure that the base glass has a lower melting temperature and a better clarification effect while having better chemical stability.
[0028] In one embodiment of the present application, the dielectric constant of the above-mentioned base glass at 25°C and 1MHz is 3.5-3.6, and the dielectric loss is 0.0001-0.0003; and / or the density of the base glass is 2.0400-2.0700 g / cm 3 .
[0029] The base glass having the above dielectric constant, dielectric loss and density is more suitable for being used as the raw material of the glass insulator in the radio frequency glass insulator.
[0030] In another typical embodiment of the present application, a method for preparing the aforementioned basic glass is provided, the preparation method comprising: mixing raw materials including Si source, B source, Al source, K source, Li source and Sn source, and then sequentially performing melting treatment and molding to obtain basic glass.
[0031] Mixing raw materials including Si source, B source, Al source, K source, Li source and Sn source and then melting them helps to form a base glass with low dielectric constant and dielectric loss. The preparation process of the above method is simple, and the temperature required for the melting treatment of the present application is lower than the temperature of the melting treatment commonly used in the prior art, and the clarification effect of the base glass is better.
[0032] In one embodiment of the present application, the temperature of the above-mentioned melting treatment is 1530-1580° C.; and / or the time of the melting treatment is 5-10 hours.
[0033] The present invention controls the contents of Si source, B source, Al source, K source, Li source and Sn source, especially controls the contents of Sn source and K source, so that the temperature of the melting process is 1530-1580°C. The prior art usually uses 1600-1650°C. The temperature of the melting process is lower than the temperature commonly used in the prior art, thereby helping to reduce the production cost of the base glass. It is preferred to control the time of the melting process within the above range, which is conducive to the melting and clarification of the base glass.
[0034] In one embodiment of the present application, the Si source is quartz sand; and / or the B source is boron gangue and / or boric acid; and / or the Al source is aluminum oxide and / or aluminum hydroxide; and / or the K source is selected from any one or more of KNO3, KF and KCl; preferably the K source is KF and / or KCl; and / or the Li source is Li2CO3; and / or the Sn source is tin dioxide.
[0035] It is preferred to control the types of Si source, B source, Al source, Li source, K source and Sn source within the above range, which helps to improve the synergy between the components and better form oxides, thereby helping to further improve the chemical stability of the base glass and reduce the dielectric constant and dielectric loss of the base glass. According to electrical theory, the dielectric constant of a material is proportional to the polarizability of the material, that is, dielectric constant = 1 + 4πα, where α represents the polarizability of the material. In other words, the lower the polarizability of the material, the smaller its dielectric constant. The present invention introduces KF and / or KCl, while avoiding the introduction of sodium ions, the main purpose of which is to reduce the polarizability of the base glass. Because the chemical properties of fluorine and / or chlorine are relatively active and have very strong electronegativity, fluorine ions and / or chloride ions can firmly bind electrons, thereby changing the base glass structure from a Si-O tetrahedral network structure to a triangular structure with weaker polarizability, that is, reducing the polarity of the base glass, thereby reducing the dielectric constant of the material. In addition, the introduction of fluoride ions and / or chloride ions can effectively reduce -OH, well control the water absorption caused by the presence of a large amount of -OH, and effectively improve the chemical stability of the base glass.
[0036] In another typical embodiment of the present application, a glass powder is provided, which includes a base glass powder. The base glass powder is prepared by subjecting the aforementioned base glass to a pulverizing treatment. Preferably, the pulverizing treatment is a ball milling treatment, and the rotation speed of the ball milling treatment is 250 to 400 rpm; and / or the ball milling treatment time is 2 to 10 hours.
[0037] The glass powder has high chemical stability. Controlling the rotation speed and time of the ball milling process within the above range helps to control the basic glass powder within a suitable range. Preferably, the ball milling process is carried out in a zirconia tank, and the grinding medium is zirconia balls, which are prepared at a ball-to-material ratio of 3:1, and anhydrous ethanol is added as a dispersion medium.
[0038] In one embodiment of the present application, the above-mentioned glass powder also includes an additive, and the mass ratio of the additive to the basic glass powder is 0.5 to 1:100; preferably, the D50 of the additive is 50 to 500 nm; and / or the D50 of the basic glass powder is 2 to 15 μm; preferably, the additive is nano-alumina and / or nano-zirconium oxide; preferably, the additive is a combination of nano-alumina and nano-zirconium oxide, and the mass ratio of nano-alumina to nano-zirconium oxide is 1:1 to 5.
[0039] The addition of additives helps to further improve the acid resistance of the glass powder. Preferably, the mass ratio of the additive to the basic glass powder is controlled within the above range, which helps to further improve the acid resistance of the glass powder. Preferably, the D50 of the additive and the basic glass powder is controlled within the above range, which helps to improve the mixing uniformity between the additive and the basic glass powder, thereby helping to further improve the acid resistance of the glass powder. Preferably, the mass ratio of nano-alumina and nano-zirconia is controlled within the above range, which helps to give full play to the synergistic effect between the two, thereby helping to further improve the acid resistance of the glass powder.
[0040] In another typical embodiment of the present application, there is provided a Figure 1 The granulated powder shown is obtained by preparing a slurry with the aforementioned glass powder, a binder and water, and then granulating it.
[0041] The mass ratio of glass powder to binder is 100:1-7; and / or the viscosity of the slurry is 150-500 Pa·s; and / or the solid content of the slurry is 50-70wt%; and / or the D50 of the granulated powder is 150-200μm; and / or the granulation treatment is pressure spray granulation or centrifugal spray granulation; and / or the binder is polyethylene glycol or polyvinyl alcohol; the D50 of the granulated powder is 150-200μm.
[0042] In another typical embodiment of the present application, there is provided a Figure 2The glass insulator is prepared by sequentially subjecting granulated powder to pressing, debinding and sintering treatments, and the granulated powder is the aforementioned granulated powder.
[0043] The debinding temperature is 350-550°C; and / or the debinding holding time is 3-5h; and / or the sintering temperature is 700-750°C; and / or the sintering holding time is 1-2h.
[0044] In another typical embodiment of the present application, a radio frequency glass insulator is provided, comprising a shell, a pin and a glass insulator, wherein the glass insulator is made of the aforementioned glass.
[0045] Since the glass insulator is made of the glass of the present application, the radio frequency glass insulator can be used in a frequency band of 40 to 60 GHz, or even in a higher frequency band.
[0046] In another typical embodiment of the present application, a radio frequency connector is provided, wherein the radio frequency connector contains the radio frequency glass insulator mentioned above.
[0047] Since the radio frequency connector contains the glass insulator made of the glass of the present application, the radio frequency connector has a longer service life, better signal transmission and lower heat generation.
[0048] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0049] Example 1
[0050] Quartz sand, boric acid, alumina, KF, Li2CO3 and tin dioxide are screened and mixed evenly. The weight of the mixture is 1 kg. The mixture is put into a platinum crucible. The platinum crucible is put into a molybdenum rod furnace. The molybdenum rod furnace is heated to 1570°C for melting. The melting and heat preservation time is 5 hours. The molten material is formed to obtain a basic glass. The basic glass contains the following components in molar percentage: 73% SiO2, 24% B2O3, The basic glass having an Al2O3 content of 0.5%, a K2O content of 0.7%, a Li2O content of 1.75%, and a SnO2 content of 0.05% is ball-milled in a zirconia jar. The grinding medium is zirconia balls, and the ball-to-material ratio is 3:1. Anhydrous ethanol is added as a dispersing medium. The basic glass powder having a D50 of 10 μm is obtained by ball-milling in a ball mill at a speed of 350 rpm for 2 hours. The basic glass powder is used as glass powder.
[0051] Example 2
[0052] The difference from Example 1 is that the base glass contains the following components: 72.65% SiO2, 24% B2O3, 0.5% Al2O3, 1% K2O, 1.75% Li2O, and 0.1% SnO2, wherein the molar ratio of K2O to SnO2 is 10:1, and the molar ratio of SiO2 to B2O3 is 1:0.33, and finally glass powder is obtained.
[0053] Example 3
[0054] The difference from Example 1 is that the base glass contains the following components: 73.41% SiO2, 23.5% B2O3, 0.5% Al2O3, 0.8% K2O, 1.75% Li2O, and 0.04% SnO2, wherein the molar ratio of K2O to SnO2 is 20:1, and the molar ratio of SiO2 to B2O3 is 1:0.32, and finally glass powder is obtained.
[0055] Example 4
[0056] The difference from Example 1 is that the base glass contains the following components: 73.75% SiO2, 23% B2O3, 0.5% Al2O3, 0.9% K2O, 1.75% Li2O, and 0.1% SnO2, wherein the molar ratio of K2O to SnO2 is 9:1, and the molar ratio of SiO2 to B2O3 is 1:0.31, and finally glass powder is obtained.
[0057] Example 5
[0058] The difference from Example 1 is that nano alumina powder is added to the basic glass powder, the D50 of the nano alumina powder is 50 nm, and the mass ratio of the nano alumina powder to the basic glass powder is 0.5:100, and finally glass powder is obtained.
[0059] Example 6
[0060] The difference from Example 1 is that nano alumina powder is added to the basic glass powder, the D50 of the nano alumina powder is 500 nm, and the mass ratio of the nano alumina powder to the basic glass powder is 1:100, and finally glass powder is obtained.
[0061] Example 7
[0062] The difference from Example 1 is that nano alumina powder is added to the basic glass powder, the D50 of the nano alumina powder is 40 nm, and the mass ratio of the nano alumina powder to the basic glass powder is 1.5:100, and finally glass powder is obtained.
[0063] Example 8
[0064] The difference from Example 1 is that nano alumina powder and nano zirconia are added to the basic glass powder, the D50 of the nano alumina powder and the nano zirconia is each independently 200 nm, wherein the mass ratio of the nano alumina and the nano zirconia is 1:1, and the ratio of the total mass of the nano alumina powder and the nano zirconia to the mass of the basic glass powder is 0.5:100, and finally glass powder is obtained.
[0065] Example 9
[0066] The difference from Example 1 is that nano alumina powder and nano zirconia are added to the basic glass powder, the D50 of the nano alumina powder and the nano zirconia is each independently 200 nm, wherein the mass ratio of the nano alumina to the nano zirconia is 1:5, and the ratio of the total mass of the nano alumina powder and the nano zirconia to the mass of the basic glass powder is 0.5:100, and finally glass powder is obtained.
[0067] Example 10
[0068] The difference from Example 1 is that nano alumina powder and nano zirconia are added to the basic glass powder, the D50 of the nano alumina powder and the nano zirconia are each independently 200 nm, wherein the mass ratio of the nano alumina to the nano zirconia is 1:0.5, and the ratio of the total mass of the nano alumina powder and the nano zirconia to the mass of the basic glass powder is 0.5:100, and finally glass powder is obtained.
[0069] Embodiment 11
[0070] The difference from Example 1 is that the rotation speed of the ball milling treatment is 250 rpm, the time of the ball milling treatment is 2 h, the D50 of the basic glass powder is 15 μm, and finally the glass powder is obtained.
[0071] Example 12
[0072] The difference from Example 1 is that the rotation speed of the ball milling treatment is 400 rpm, the time of the ball milling treatment is 10 h, the D50 of the basic glass powder is 2 μm, and the glass powder is finally obtained.
[0073] Embodiment 13
[0074] The difference from Example 1 is that the temperature of the melting treatment is 1530° C., the time of the melting treatment is 10 h, and finally glass powder is obtained.
[0075] Embodiment 14
[0076] The difference from Example 1 is that the temperature of the melting treatment is 1580° C., the time of the melting treatment is 5 hours, and finally glass powder is obtained.
[0077] Embodiment 15
[0078] The difference from Example 1 is that the temperature of the melting treatment is 1600° C., the time of the melting treatment is 4 hours, and finally glass powder is obtained.
[0079] Example 16
[0080] The difference from Example 1 is that KNO3 is used to replace KF, and glass powder is finally obtained.
[0081] Comparative Example 1
[0082] The difference from Example 1 is that the base glass contains the following components: 77.9% SiO2, 19% B2O3, 0.6% Al2O3, 0.4% K2O, 1.7% Li2O, and 0.4% SnO2, and finally glass powder is obtained.
[0083] Comparative Example 2
[0084] The difference from Example 1 is that the base glass is prepared by the method of Example 1 in the Chinese patent with patent authorization announcement number CN113121119B, and the components of the base glass are, in molar percentage, SiO2: 71%, B2O3: 23%, Ga2O3: 1.0%, P2O5: 1.0%, Li2O: 2.0%, K2O: 1.0%, LaB6: 0.7%, and NaCl: 0.15%, and finally glass powder is obtained.
[0085] Performance Testing
[0086] Dielectric constant and dielectric loss: At 25°C and 1MHz, the test method of SJT 11043GB 9622 electronic glass high-frequency dielectric loss and dielectric constant is adopted.
[0087] Acid resistance: GBT 15728-1995 Gravimetric test method and classification of glass resistance to boiling hydrochloric acid corrosion is adopted.
[0088] The dielectric constant, dielectric loss and density of the base glass prepared in the above embodiments and comparative examples were tested. The acid resistance of the glass powder prepared in the above embodiments and comparative examples was tested. The test results are shown in Table 1.
[0089] Table 1
[0090]
[0091] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0092] SiO2 and B2O3 are network formers of the basic glass. SiO2 is the main component of the basic glass and exists in the form of [SiO4], while B2O3 exists in the form of [BO3] and [BO4], where [BO4] and [SiO4] are connected to make the glass network structure more stable, which is beneficial to improve the chemical stability of the basic glass. On the other hand, since the network structure of SiO2 and B2O3 is relatively stable and the covalent bonds are relatively strong, it is difficult for electrons and ions to move or undergo significant polarization reactions, which can significantly reduce the dielectric constant of the glass. Al2O3, as a filler in the network structure, helps to adjust the chemical stability of the basic glass and helps to reduce the phase separation of the glass. K2O and Li2O, as network exogenous bodies of the glass, will destroy the network structure of the glass, help to reduce the melting temperature of the glass and improve the clarification effect of the glass. In addition, K + Ions have a larger ionic radius than Na + The ions are large, so their movement in the limited glass network structure is restricted, so their impact on the dielectric constant is greater than that of Na + Ions should be low; Li + The ionic radius is the smallest among alkali metals, and the polarization ability is weak. It can be tightly combined with the silicon-oxygen bond in the glass network structure, thereby reducing the polarization ability of the glass. Therefore, a small amount of addition will not have a significant impact on the dielectric constant of the glass. At the same time, it can also effectively reduce the melting temperature of the glass and improve the chemical stability. SnO2 is added to the glass as a glass clarifier, and the bubbles in the glass are eliminated by high-temperature decomposition and release of oxygen. It is preferred to control the content of the above components within the above range, which helps to give full play to the synergistic effect between the components, thereby helping to improve the chemical stability of the base glass and reduce the dielectric constant and dielectric loss of the base glass. In particular, controlling the content of K2O to 0.5-1% and the content of SnO2 to 0.01-0.1% helps to give full play to the synergistic effect between the two, thereby helping to reduce the melting temperature of the base glass and improve the clarification effect of the base glass.
[0093] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A basic glass, characterized in that: In terms of molar percentage, the base glass includes the following components: 72-74% SiO2, 20-25% B2O3, 0.1-0.5% Al2O3, 0.5-1% K2O, 1.8-2.2% Li2O, and 0.01-0.1% SnO2.
2. The base glass according to claim 1, characterized in that: The molar ratio of the K2O to the SnO2 is 10-20:1; and / or the molar ratio of the SiO2 to the B2O3 is 1:0.32-0.
33.
3. The base glass according to claim 1 or 2, characterized in that: The dielectric constant of the base glass at 25° C. and 1 MHz is 3.5 to 3.6, and the dielectric loss is 0.0001 to 0.0003; and / or the density of the base glass is 2.0400 to 2.0700 g / cm 3 .
4. A method for preparing the base glass according to any one of claims 1 to 3, characterized in that: The preparation method comprises: mixing raw materials including Si source, B source, Al source, K source, Li source and Sn source, and then melting and molding them in sequence to obtain the basic glass.
5. The preparation method according to claim 4, characterized in that: The temperature of the melting treatment is 1530-1580° C.; and / or the time of the melting treatment is 5-10 hours.
6. The preparation method according to claim 4 or 5, characterized in that: The Si source is quartz sand; And / or, the B source is boron ore and / or boric acid; And / or, the Al source is aluminum oxide and / or aluminum hydroxide; And / or, the K source is selected from any one or more of KNO3, KF and KCl; preferably, the K source is KF and / or KCl; And / or, the Li source is Li2CO3; And / or, the Sn source is tin dioxide.
7. A glass powder, characterized in that: The glass powder includes basic glass powder, and the basic glass powder is prepared by crushing the basic glass described in any one of claims 1 to 3, preferably the crushing treatment is ball milling treatment, the rotation speed of the ball milling treatment is 250 to 400 rpm; and / or the time of the ball milling treatment is 2 to 10 hours.
8. The glass powder according to claim 7, characterized in that The glass powder further includes an additive, and the mass ratio of the additive to the basic glass powder is 0.5 to 1:100; Preferably, the D50 of the additive is 50-500 nm; and / or the D50 of the base glass powder is 2-15 μm; Preferably, the additive is nano-alumina and / or nano-zirconium oxide; Preferably, the additive is a combination of the nano-aluminum oxide and the nano-zirconia, and the mass ratio of the nano-aluminum oxide to the nano-zirconia is 1:1-5.
9. A granulated powder, characterized in that The glass powder according to claim 7 or 8 is prepared into a slurry with a binder and water, and then granulated.
10. A glass insulator, prepared by sequentially pressing, debinding and sintering granulated powder, characterized in that: The granulated powder is the granulated powder according to claim 9.
11. A radio frequency glass insulator, comprising a housing, a pin and a glass insulator, characterized in that: The glass insulator is the glass insulator according to claim 10.
12. A radio frequency connector, characterized in that: The radio frequency connector contains the radio frequency glass insulator according to claim 11.
Citation Information
Patent Citations
Low dielectric constant glass powder and preparation method thereof
CN109399937A
A low-dielectric sealing glass powder for miniature radio frequency glass insulators
CN113121119B